2015
DOI: 10.1063/1.4919127
|View full text |Cite
|
Sign up to set email alerts
|

Extended law of corresponding states for protein solutions

Abstract: The so-called extended law of corresponding states, as proposed by Noro and Frenkel [J. Chem. Phys. 113, 2941 (2000)], involves a mapping of the phase behaviors of systems with short-range attractive interactions. While it has already extensively been applied to various model potentials, here we test its applicability to protein solutions with their complex interactions. We successfully map their experimentally determined metastable gas-liquid binodals, as available in the literature, to the binodals of short-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 130 publications
(295 reference statements)
8
81
0
Order By: Relevance
“…To compare gliadins with others proteins, we calculate the reduced second virial coefficient B 2 * = B 2 / B 2, HS , with B 2, HS the second virial coefficient of the equivalent hard sphere. B 2, HS is equal to 2/3 πσ eff 3 with σ eff the effective diameter accounting for hard core and electrostatic repulsion 60 , 61 . The effective radius of gliadins is about 3.3 +/−0.3 nm as determined in Supplementary data 2 based on our previous results of osmotic compressibility 27 .…”
Section: Resultsmentioning
confidence: 99%
“…To compare gliadins with others proteins, we calculate the reduced second virial coefficient B 2 * = B 2 / B 2, HS , with B 2, HS the second virial coefficient of the equivalent hard sphere. B 2, HS is equal to 2/3 πσ eff 3 with σ eff the effective diameter accounting for hard core and electrostatic repulsion 60 , 61 . The effective radius of gliadins is about 3.3 +/−0.3 nm as determined in Supplementary data 2 based on our previous results of osmotic compressibility 27 .…”
Section: Resultsmentioning
confidence: 99%
“…105,106 In fact, many theoretical models do require incorporation of charge-charge interactions for adequately fit experimental liquid-liquid binodal curves. 106,107 Interestingly, if one considers the average size of a globular protein (~ 4 nm), those PLFs with broad coexistence curves and similar values for the dipole moment (e.g., triangles and squares in Figs. 6 and 7) qualitatively capture the main characteristics of experimental protein phase behavior.…”
Section: Discussionmentioning
confidence: 99%
“…26 Originally proposed by Noro and Frenkel for isotropic particles exhibiting macroscopic phase separation, ECS is a useful way to draw comparisons between models and identify which ones are essentially equivalent. 26,27 Foffi and Sciortino found that patchy particles also obey ECS near the gas-liquid critical point. 28 In addition, ECS has been used to study the phase behavior of active particle suspensions.…”
Section: Introductionmentioning
confidence: 99%